Functional balance training in people with Parkinson’s disease: a protocol of balanceHOME randomized control trial with crossover - Monleón Guinot, Sara; San Martín Valenzuela, Constanza; Aranda Asensi, Vivina; de Salazar Antón, Concepción; Villanueva Navarro, Manuel; Tomás, Jose M. (Frontiers in Aging Neuroscience, 2023)
Introduction Balance disturbances in Parkinson’s Disease (PD) are usually assessed in a single-task as well as standard balance physiotherapy is carried out in isolated environments. Conversely, daily activities are developed in highly challenging environments. Although functional balance training (FBT) is included in the latest protocols, several methodological issues have not yet been considered. In the proposed single-blinded randomized control trial with crossover (NCT04963894), the aims are (1) to quantify the effects achieved by domiciliary FBT (balanceHOME program) in participants with and without cognitive impairment, and (2) to compare them with the effects of a passive-control period and a conventional face-to-face physiotherapy program for PD. Methods The initial recruitment was estimated at 112 people with idiopathic PD. Two-thirds of the participants will be randomized to one of the two groups to make the crossover. In contrast, the other third will do a face-to-face group program only. The balanceHOME protocol consists of challenging balance exercises incorporated into functional daily tasks, developed in-home and conducted two times per week for 60-min over an 8-weeks period. The primary strategy will consist of splitting functional tasks of daily life into static and dynamic balance components, besides standardized facilitate and disturbing strategies to execution of each exercise. Biomechanics and clinical performance of balance and gait, perception of quality of life, cognitive and mental functioning, and severity of PD will be measured at baseline (T0), post-8 weeks training (T1), and follow-up (T2). Results The primary outcome of the study will be the center of pressure sway area. The secondary outcomes consist of biomechanics and clinical variables related to static and dynamic balance. Outcomes from biomechanical of gait, quality of life, cognitive and mental state, and severity of PD, represent the tertiary outcomes. Discussion The balanceHOME program standardizes the FBT in demanding and daily environments for people with PD who prefer individualized treatment from home. This is the first time that the effects of group versus individual balance rehabilitation have been compared in people with and without cognitive impairment and evaluated in complex environments. This still-to-be-finished study will open the possibility of new strategies according to changes in post-pandemic therapeutic approaches.